Balancing the Conspiracy’s Books: Inter-Competitor Sales and Price-Fixing Cartels - Christopher R. Leslie (Washington University Law Review, 2018)
Price fixing is antithetical to a free-market economy. Competitive markets supply goods and services to consumers at the lowest efficient prices. Unfortunately, many businesses would prefer not to compete because they can increase their profits by conspiring to raise price. By refraining from competition, each firm in a price-fixing cartel can maximize its profits at the expense of its customers. Price-fixing conspiracies injure consumers by reducing output below the efficient level and transferring wealth from consumers to conspirators. Fortunately, cartels are often unstable because each member of the conspiracy can maximize its short-term profits by cheating on the cartel agreement by selling more than its cartel allotment or charging less than the cartel price. Cartels try to create stability through enforcement regimes. In order to deter cheating and to remedy cheating when it occurs, stable cartels need to develop enforcement mechanisms that monitor the sales (and prices) of cartel members, penalize firms that sell more than their cartel allotment, and compensate those who have not received their agreed-upon share of the cartel profits. Common monitoring schemes include firms hiring a third-party auditor or reporting their sales figures to a central cartel manager. When such monitoring detects deviations from the assigned cartel quotas, a cartel ringleader may require those firms that have oversold to funnel money to their cartel partners that have undersold. When cartel managers can solve the enforcement problems inherent in price-fixing conspiracies, cartels can survive for decades. Depending on the size of the market that has been cartelized, price-fixing conspirators can overcharge their consumers by billions of dollars. And while some consumers are being fleeced, other consumers are priced out of the market altogether and denied access to products and services that they would be able to purchase in a truly competitive market. Antitrust law is designed to deter and dismantle price-fixing cartels. Section One of the Sherman Act condemns price-fixing agreements as per se illegal. Section One is both a criminal and a civil statute. If criminally convicted, individuals face up to ten years’ imprisonment. Corporations convicted of price fixing are subject to fines of nine figures or higher. On the civil side, consumers who paid illegally inflated prices can sue for the overcharge. Antitrust damages are automatically tripled, and successful plaintiffs are entitled to their attorneys’ fees and costs. When the threat of enforcement of antitrust laws is genuine, rational firms can be dissuaded from conspiring to fix prices. When firms nonetheless persevere in their price fixing, effective antitrust enforcement can disgorge the ill-gotten gains and compensate the victims of the price-fixing conspiracy. The success of the antitrust regime depends on courts being able to recognize price fixing and to hold price fixers accountable. Unfortunately, courts often do not appreciate the mechanics of cartelization. Most federal judges have not studied the theory and practice of price fixing. They are unfamiliar with the ubiquity of international cartels and the case studies of price fixing in American history. More importantly, judges are generally unversed in how conspirators structure cartel activities to avoid detection or to appear innocent to outsiders untrained in the art of price fixing. This gives actual price fixers confidence that they can conspire to illegally restrain competition while evading liability in court. This Article focuses on the legal significance of competitors buying products from each other. Such inter-competitor sales stabilize price-fixing conspiracies by providing a mechanism to balance the cartel’s books. When one price-fixing conspirator sells more than its cartel quota to its customers, the other conspirator firms that have undersold will demand some form of compensation. Absent some form of reimbursement, an underselling firm may decide the risks of price fixing are not worth the benefits, which are now less than negotiated when its partners are not honoring the letter of the agreement. If one major firm leaves the cartel, the entire enterprise may collapse, and all of the firms may find themselves in a competitive market. To avoid that scenario, some price-fixing conspiracies arrange to have over-sellers purchase products from under-sellers, which funnels money from the former to the latter. This can preserve the life of the cartel, improving the cartel’s coffers at its customers’ expense. If federal judges do not understand how price-fixing conspiracies use inter-competitor sales to enforce their cartel arrangements, then judges may be more prone to dismiss price-fixing claims or grant summary judgment to defendants who have, in fact, conspired to fix prices. This Article seeks to reduce the likelihood of that outcome by explaining how cartels use inter-competitor sales—sometimes called buybacks or true-ups—as a mechanism to balance the cartel’s books. Using a combination of economic analysis and empirical case studies, this Article examines the critical role that buybacks can play—and have played—in price-fixing conspiracies. Part One of this Article lays out the legal framework for proving price fixing through circumstantial evidence. Because direct evidence of price fixing is rarely available, most plaintiffs rely on circumstantial evidence, which requires them both to show that the defendants engaged in parallel pricing and to present “plus factors.” Plus factors are types of evidence that indicate that the parallel conduct is a function of collusion, not of independent decision-making. Through the common-law process, federal courts have recognized over a dozen different plus factors. Part Two discusses how courts have addressed the significance of inter-competitor sales as evidence of a price-fixing conspiracy. Until recently, all federal courts to consider the issue have held inter-competitor sales to be a plus factor. These opinions, however, generally have little discussion about the mechanics of cartelization and how price-fixing conspirators often purchase products from each other as a way to balance accounts among cartel members. Nevertheless, the law seemed reasonably settled. In 2017, however, in Valspar Corp. v. E.I. Du Pont De Nemours & Co., a divided panel of the Third Circuit—claiming a lack of precedent on the issue—held that inter-competitor sales among manufacturers of titanium dioxide had no probative value, and consequently affirmed summary judgment for the defendants, even though the defendants had engaged in thirty-one parallel price increases and other plus factors were present. The Valspar opinion risks upending settled precedent, while claiming that no such precedent exists. Using both economic theory and empirical evidence, Part Three explains why inter-competitor sales are inherently probative of collusion. To be stable in the long run, a price-fixing conspiracy requires a mechanism for cartel members who sell more than their quota to compensate their under-selling cartel partners. Inter-competitor sales provide an ideal compensation instrument because buybacks funnel money from one firm to its rivals without appearing as suspicious as a one-way cash transfer. Inter-firm transactions provide a plausible excuse for why competitors are meeting and discussing the price of their products. Also, buying from rivals removes product from the market in order to create artificial scarcity and, thereby, drives up the market price. Empirically, actual price-fixing cartels have used inter-competitor sales to balance their books. For example, in the early and mid-twentieth century, the international cartels in dyestuffs and aluminum employed company-to-company sales to ensure that each cartel member received its agreed-upon shares of the cartel’s profits. More recently, modern price-fixing conspiracies in citric acid, lysine, and vitamins—which collectively overcharged their customers by billions of dollars—used inter-competitor sales as a cartel enforcement mechanism. Part Four examines the Third Circuit’s Valspar opinion in detail. In discounting inter-competitor sales as a plus factor, the Third Circuit committed several errors. It is important to expose and explain these errors so that future federal judges do not follow in the Third Circuit’s footsteps and replicate these mistakes. For example, the Valspar opinion created the false impression that no precedents or studies exist showing the link between inter-competitor sales and price-fixing conspiracies. It also misanalysed the facts before it, for example, by seeming to treat the presence of intellectual property licensing agreements as sapping inter-competitor sales of their probative value. Ultimately, because the Valspar majority did not understand how price-fixing conspiracies operate, the opinion failed to appreciate the legal significance of inter-competitor sales. Finally, Part Five explains how inter-competitor sales are an important plus factor that help demonstrate that the defendants’ parallel pricing is the product of collusion, not independent decision-making. The presence of inter-competitor sales is a plus factor, in and of itself, because cartels commonly use them as an enforcement device. Such sales also help establish other recognized plus factors, including conduct against the parties’ independent economic interests. Part Five concludes by explaining how the probative value of inter-competitor sales increases significantly under certain conditions, including when the purchasing firm has inventory or excess capacity, when the transactions are correlated with the competing firms reporting their sales data to each other, when the market is characterized by stable market shares, and when the inter-competitor sales take place at non-market prices.
Keywords: Price fixing; cartel; Sherman Act; Antitrust law; Sherman Antitrust Act; competition; markets; Valspar; Valspar Corp. v. E.I. Du Pont De Nemours & Co. 873 F.3d 185 (3d Cir. 2017); inter-competitor sales; Inter-firm transactions; price-fixing conspiracies; Plus-Factor Analysis; Non-Market Prices